PLEISTOCENE DEGLACIATION CHRONOLOGY OF THE AMERY OASIS AND RADOK LAKE, NORTHERN PRINCE CHARLES MOUNTAINS, ANTARCTICA - Fink D.; McKelvey B.; Hambrey M.J.; Fabel D.; Brown R. (My University, 2006)
The East Antarctic Ice Sheet is the largest ice mass on Earth with a capacity to raise global sea level by up to 65 m. As the Lambert Glacier-Amery Ice Shelf drainage system is the largest to reach the coast of Antarctica, quantifying its evolution over the Quaternary is a vital component in developing an understanding of the Antarctic response to future climate change. Here we present a deglaciation chronology based on 10Be and 26Al in situ cosmogenic exposure ages of the northern Prince Charles Mountains, which flank the Lambert Glacier-Amery system, and that records the progressive emergence of McLeod Massif and Radok Lake basin from beneath the Mac.Robertson Land lobe of the East Antarctic Ice Sheet. The exposure ages monotonically decrease with both decreasing altitude and increasing proximity to the Amery Ice Shelf at the Antarctic coast. Exposure ages from the crests of McLeod Massif near the edge the Amery Ice Shelf and from Fisher Massif, 75 km further inland, each at ~1200 m above sea level, are 2.2 ± 0.3 and 1.9 ± 0.2 Ma, respectively, suggesting their continuous exposure above the ice sheet at least since close to the Plio-Pleistocene boundary. An extensive plateau at ~800 m altitude on McLeod Massif above Battye Glacier records the massif's increased emergence above the ice sheet surface at about between 880 and 930 ka ago indicating 400 m of ice volume reduction in the mid Pleistocene. Correcting these apparent ages for a reasonable choice in erosion rate would extend this event to ~1.15 Ma - a period identified from Prydz Bay ODP core-1167 when sedimentation composition alters and rates decrease 10-fold. Exposure ages from boulder-mantled erosional surfaces above and beyond the northern end of Radok Lake at 220 m, range from 28 to 121 ka. Independent of choice of model interpretation to explain this age spread, the most recent major reoccupation of Radok Lake by Battye Glacier ice occurred during the last glacial cycle. Moraine ridges at the lower altitude of 70-125 m were deposited during the final withdrawal of Battye Glacier ice from the lake basin between 11 and 20 ka ago. This new chronology indicates that the highest Amery Oasis peaks have not been overridden by the Mac.Robertson Land lobe of the East Antarctic Ice Sheet for at least the past 2 Ma. Since this time we document 3 major periods of regional reduction in ice sheet volume at ~1.1 Ma, during the last glacial cycle (120 to 30 ka) and through the Last Glacial Maximum (20 to 10 ka) that resulted in an overall 1000 m of ice owering in the Battye Glacier-Radok Lake region. © 2006 Elsevier B.V. All rights reserved.
Keywords: COSMOGENIC ISOTOPES; EAST ANTARCTIC ICE SHEET; NORTHERN PRINCE CHARLES MOUNTAINS; PLEISTOCENE GLACIAL CHRONOLOGY; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Quaternary::Pleistocene